(3JMQjQ GdeYWjGJ dEbdjOSs - (3GbdjOSs
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI UOQ GdcJGH GdSWhM hGdNWhW hGdRhGjG GdeYdheI GdbOQ gj GdJj jecf Gf JLO eSGhjI dgG s
(3BNQgG (B:s
(3afbWI (B200 (3eYdheI hGdOGFQI eYdheI GdhVY hbO eQ ajgG (B81 s
(3Vef eLehY , JQJjHgG (B: 4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3GjGUhajG (B(1760) s
Keywords: (3eJaQbGJs